2018
DOI: 10.1155/2018/4390318
|View full text |Cite
|
Sign up to set email alerts
|

Western Blot-Based Logistic Regression Model for the Identification of Recent HIV-1 Infection: A Promising HIV-1 Surveillance Approach for Resource-Limited Regions

Abstract: Objectives Identifying recent infections is necessary to monitor HIV/AIDS epidemic; however, it needs to be further developed. Methods and Results Participants were defined as having recent infection or older infection according to the estimated duration of HIV-1 infection and further assigned into training set and validation set according to their entering time points. Western blot (WB) confirmatory test and BED-CEIA were performed. The performance of the two methods on recent HIV-1 diagnosis was evaluated an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 25 publications
1
8
0
Order By: Relevance
“…They are able to detect HIV specific antibodies in most subjects, but acute HIV infection and late-stage HIV infection maybe negative or indeterminate for HIV antibody tests [ 3 , 21 – 23 ]. Previous studies have proven that the sequential emergence of HIV-1 antibodies associates with the progress of HIV-1 infection [ 11 , 12 , 24 – 26 ], therefore the laboratory diagnosis of HIV infection is helpful for understanding the local epidemic and may partly reflect the effectiveness of HIV/AIDS intervention. Our data indicated that, although the number of suspected samples gradually grown in Wuhan, the positive rate of HIV-1 antibodies has declined significantly during 2012–2018.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…They are able to detect HIV specific antibodies in most subjects, but acute HIV infection and late-stage HIV infection maybe negative or indeterminate for HIV antibody tests [ 3 , 21 – 23 ]. Previous studies have proven that the sequential emergence of HIV-1 antibodies associates with the progress of HIV-1 infection [ 11 , 12 , 24 – 26 ], therefore the laboratory diagnosis of HIV infection is helpful for understanding the local epidemic and may partly reflect the effectiveness of HIV/AIDS intervention. Our data indicated that, although the number of suspected samples gradually grown in Wuhan, the positive rate of HIV-1 antibodies has declined significantly during 2012–2018.…”
Section: Discussionmentioning
confidence: 99%
“…The emergence of HIV antibodies presents the infection status. Studies had proved that the number, intensity, and the order of appearance of HIV antibodies in blood were associated with the stage of HIV-1 infection [10,11]. Recently, we had estimated the seroconversion time of HIV-1 antibodies from a clinical observation and found that both p31 and p66 antibodies were potential serologic biomarkers of recent HIV-1 infection [12].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Sensitivity of 83.3% and specificity of 96.7% were demonstrated by the assay using 30 sera from confirmed Chikungunya virus infected patient and 30 normal sera [ 144 ]. In one study, western blotting was a promising method for surveillance of HIV-1 infection in resource-limited regions [ 145 ]. The assay was also used for the detection and confirmation of HCV and HIV infections [ 146 – 148 ].…”
Section: Immunological Diagnostic Techniques Of Medical Virusesmentioning
confidence: 99%